Comparative study of the glycosylation of platelet glycoprotein GPIIb/IIIa and the vitronectin receptor. Differential processing of their beta-subunit. - Troesch, A (1990)
The platelet glycoprotein GPIIb/IIIa and the vitronectin receptor (VNR) are alpha beta-heterodimeric proteins and share the same beta-subunit. By performing swainsonine treatment and digestion with endoglycosidase H (Endo H), we showed that the heavy chains of GPIIb and VNR alpha are glycosylated by complex-type oligosaccharide chains, and provided the first evidence for the presence of one complex carbohydrate residue on their light chains. The proteolytic cleavage of pro-GPIIb and the acquisition of Endo H-resistance are independent events occurring in the same Golgi compartment. We demonstrated the Endo H-sensitivity of GPIIIa and VNR beta in all cellular systems tested. In addition, this beta-subunit is differently glycosylated according to whether it is associated with GPIIb or VNR alpha, one carbohydrate chain being processed to the complex type on GPIIIa, but not on VNR beta.